2008
DOI: 10.1016/j.febslet.2008.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Residue 134 determines the dimer–tetramer assembly of nucleoside diphosphate kinase from moderately halophilic bacteria

Abstract: Halomonas nucleoside diphosphate kinase (HaNDK) forms a dimeric assembly and Pseudomonas NDK (PaNDK) forms a tetrameric assembly. The mutation of Glu134 to Ala in HaNDK resulted in the conversion of the native dimeric structure to the tetramer assembly. Conversely, the mutation of Ala134 to Glu in PaNDK lead to the conversion from the tetramer to the dimer assembly, indicating that a single amino acid substitution at position 134 results in an alteration of the oligomeric structure of NDK. By modeling the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…In this expression of NDK/XX, the first X after the slash represents the 134th residue and the second X represents the 135th residue, with the mutated residue underlined. The cross-linking results were confirmed by sedimentation velocity analysis (Tokunaga et al, 2008b). The size distribution analysis showed a dimeric molecular mass of HaNDK and a tetrameric molecular mass of PaNDK.…”
Section: Dimer-tetramer Conversion Of Handk and Pandksupporting
confidence: 50%
See 1 more Smart Citation
“…In this expression of NDK/XX, the first X after the slash represents the 134th residue and the second X represents the 135th residue, with the mutated residue underlined. The cross-linking results were confirmed by sedimentation velocity analysis (Tokunaga et al, 2008b). The size distribution analysis showed a dimeric molecular mass of HaNDK and a tetrameric molecular mass of PaNDK.…”
Section: Dimer-tetramer Conversion Of Handk and Pandksupporting
confidence: 50%
“…Based on high sequence homology between halophilic Halomonas sp. 593NDK (HaNDK) and nonhalophilic Pseudomonas aeruginosa NDK (PaNDK) and the modeled atomic structure, we have mutated residues involved in oligomer assembly of the two NDKs above and observed that a single mutation can cause nonhalophilic tetrameric PaNDK to dissociate into the dimer and halophilic dimeric HaNDK to assemble into the tetramer (Tokunaga et al, 2008b) as reported in this review.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of crystal structures shows that in the type 2 tetramer, (46) the Kpn/α 0 foldon is located at the dimer-dimer interface and has the same control switch role. On the contrary, in type 1 tetramer (66) and dimer, (47,67,68) the Kpn/α 0 foldon is fully exposed and could not have such a regulatory role. High eukaryotes have several isoforms of NDPK with additional functions: metastasis suppression in humans (35,36,69,70) and involvement in animal development.…”
Section: Discussionmentioning
confidence: 99%
“…(42,43) NDPKs contain ferredoxin-like folds (45) which assemble first as dimers and then as tetramers or hexamers. (46)(47)(48) Tetramers are present in gram-negative bacteria and archaea, while hexamers are present in gram-positive bacteria and eukaryotes. Hexamers represent the most abundant type of oligomerization, which specifically relies on the well conserved surface loop that carries the site of the natural "Killer of prune" mutation (Kpn-loop) (Figures 1, S1).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent molecular mass of His-KvSBD12 on SDS-PAGE (14% Laemmli gel) was ∼40 kDa, which was much higher than the true molecular mass, 23 kDa. This slow mobility on SDS-PAGE is one of the characteristics of halophilic proteins [29], due to abnormally weak SDS binding [30]. A single domain KvSBD1 with amino-terminal hexa-His-tag (His-KvSBD1, Fig.…”
Section: Expression and Purification Of Kvsbdmentioning
confidence: 99%